Macrophage and Innate Lymphoid Cell Interplay in the Genesis of Fibrosis - Hams, Emily; Bermingham, Rachel; Fallon, Padraic G. (Frontiers in Immunology, 2015)
Fibrosis is a characteristic pathological feature of an array of chronic diseases, where development of fibrosis in tissue can lead to marked alterations in the architecture of the affected organs. As a result of this process of sustained attrition to organs, many diseases that involve fibrosis are often progressive conditions and have a poor long-term prognosis. Inflammation is often a prelude to fibrosis, with innate and adaptive immunity involved in both the initiation and regulation of the fibrotic process. In this review we will focus on the emerging roles of the newly described innate lymphoid cells (ILC) in the generation of fibrotic disease with an examination of the potential interplay between ILC and macrophages and the adaptive immune system.